2018
DOI: 10.1680/jstbu.16.00192
|View full text |Cite
|
Sign up to set email alerts
|

Study of composite steel frame with reinforced-concrete infill

Abstract: This paper describes the development of a three-dimensional, non-linear finite-element model for evaluating the response of composite structural systems consisting of steel frames with reinforced-concrete infill walls subjected to a combination of gravity and in-plane lateral loading. Several sensitivity studies, taking into account both material characteristics and geometrical non-linearities were performed in order to investigate parameters such as the shear retention factors, Coulomb's coefficient for steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Finally, the last paper of this particular issue (Vogiatzis and Avdelas, 2018) also focuses on the concrete infill of steel frames and presents the development of a three-dimensional, non-linear finite-element model to assess the structural behaviour of steel frames with reinforced-concrete infill walls subjected to a combination of gravity and in-plane lateral loading. Sensitivity studies, taking into account both material characteristics and geometrical non-linearities were made to study parameters like the shear retention factors, Coulomb's coefficient for steel-concrete contacts and different load-slip relationships for modelling the shear behaviour of headed studs.…”
Section: Structures and Buildingsmentioning
confidence: 99%
“…Finally, the last paper of this particular issue (Vogiatzis and Avdelas, 2018) also focuses on the concrete infill of steel frames and presents the development of a three-dimensional, non-linear finite-element model to assess the structural behaviour of steel frames with reinforced-concrete infill walls subjected to a combination of gravity and in-plane lateral loading. Sensitivity studies, taking into account both material characteristics and geometrical non-linearities were made to study parameters like the shear retention factors, Coulomb's coefficient for steel-concrete contacts and different load-slip relationships for modelling the shear behaviour of headed studs.…”
Section: Structures and Buildingsmentioning
confidence: 99%
“…From the literature reviews presented by the authors [7,8], it appeared that although some reported experimental studies could be found in [11,12], very limited analytical or theoretical investigation was reported on the behaviour of the SRCW-T2 system. On this basis it is necessary to undertake further comprehensive investigations to better understand the flexural behaviour of composite SRCW-T2 systems.…”
Section: Objective and Approachmentioning
confidence: 99%
“…The generated three-dimensional (3D) finite element (FE) model used to perform the parametric study has been recently developed and validated by the authors (Figure 2b) for computing the behaviour of tested specimens. The details of the 3D FE models and their validation using experimental results are discussed in detail in [7]. These validated models were developed using the Finite Element Method (FEM) and provided further insight into the behaviour of composite SRCW-T2 systems.…”
Section: Prior Analytical Researchmentioning
confidence: 99%
See 2 more Smart Citations